Catalyst carrier, composite catalyst, preparation method thereof, fuel cell and application thereof

By uniformly loading platinum particles on the mesoporous C support to form Fe-N-C composite catalyst, the problem of insufficient activity and stability of carbon support in fuel cells is solved, high oxygen reduction activity and stability is achieved, and the preparation process is simplified .

CN113363516BActive Publication Date: 2025-01-14THE HONG KONG UNIV OF SCI & TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202110234515.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-03-04
Filing Date
2021-03-03
Publication Date
2025-01-14
Estimated Expiration
2041-03-03

AI Technical Summary

Technical Problem

It is difficult for existing carbon support to achieve high specific surface area, high graphitization degree and suitable mesoporous structures in fuel cells, resulting in insufficient oxygen reduction activity and stability of the catalyst.

Method used

Using mesoporous C doped with single atoms of transition metals (such as Fe) and non-metallic elements (such as N, S, P) as a carrier, the high load of precious metals (such as platinum) particles are uniformly loaded through formic acid reduction method to form Fe -N-C composite catalyst.

Benefits of technology

The oxygen reduction activity and stability of the catalyst are improved, the utilization rate of active sites is enhanced, the preparation process is simplified, and the subsequent treatment of auxiliary agents is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113363516B_ABST
    Figure CN113363516B_ABST
Patent Text Reader

Abstract

The present invention provides a catalyst carrier, a composite catalyst, a method for preparing the composite catalyst and an application thereof. The catalyst carrier comprises a mesoporous carbon-containing matrix doped with at least one non-metallic element selected from Groups VA, VIA and VIIA in the periodic table, and further comprises an active site dispersed with at least one transition metal single atom. In the catalyst carrier of the present invention, the transition metal is uniformly dispersed in the carrier as a single-atom active site, thereby improving the utilization rate of the active site.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a novel catalyst carrier, a composite catalyst, a preparation method thereof, a fuel cell and applications thereof, and more specifically to an Fe-NC catalyst carrier, a composite catalyst having oxygen reduction catalytic activity comprising an active carrier and noble metal (e.g., platinum particles), a preparation method thereof and applications thereof in a fuel cell, and particularly to a composite catalyst using Fe-NC with a large specific surface area, a high degree of graphitization and a reasonable pore structure as a carrier to load fine platinum particles (e.g., platinum particles of 2-30 nm, preferably 2-4 nm), a preparation method thereof and applications thereof in a fuel cell. Background Art

[0002] Fuel cell catalysts usually include carbon carriers and precious metal-based particles (especially platinum particles). Traditional carbon carriers are mainly divided into non-porous and porous carbon. Among them, Vulcan carbon, acetylene black and highly graphitized carbon are non-porous carbon, while Ketjen black and oxidized acetylene black are usually used as porous carbon. However, these carbon carriers are usually prone to being poisoned by ionomers, and have high transport resistance to substances such as oxides or reactants (such as oxygen) when used as catalyst carriers.

[0003] There have been attempts to improve the performance of carbon supports. [1] In, Shelef reported a noble metal catalyst supported by a zeolite carrier containing continuous rich conductive channels. U.S. Patent No. 7,432,221 [2] In the study, Kim et al. regulated the pore size of the carrier to range, thereby reducing the poisoning effect of the oxidized state in the fuel cell. [3] Sun et al. reported a nanocarbon ring with high specific surface area and high degree of graphitization. [4] In the patent application No. 2013 / 148558, Zhu et al. introduced a composite carbon support comprising carbon particles and carbon nanowires. [5] et al. reported a high specific surface area boron-doped diamond support to improve the antioxidant capacity of the catalyst.

[0004] However, these methods require tedious preparation and the carbon supports still cannot simultaneously achieve high specific area, high degree of graphitization, suitable mesoporous structure and improved overall oxygen reduction activity of the catalyst.

[0005] Therefore, there is still a need for a catalyst carrier that contains active sites and is conducive to uniform dispersion of particles for preparing a composite catalyst in which the carrier and the metal catalyst act synergistically.

[0006] Patent Literature:

[0007] [1] Shelef, Mordecai. "Fuel cell electrode comprising conductive zeolitesupport material." US Patent No. 6, 117, 581.12 Sep. 2000.

[0008] [2] Kim, Chang-Soo, et al. "Electrocatalyst for fuel cells using supportbody resistant to carbon monoxide poisoning." USPatent No.7,432,221.7Oct.2008.

[0009] [3] Sun, Gongquan, et al. "Fuel cells and fuel cell catalystsincorporating a nanoring support." USPatent No.8,133,637.13 Mar.2012.

[0010] [4]Zhu, Yimin, et al. "Nanostructured catalyst supports." USPatentNo.8,278,011.2 Oct.2012.

[0011] [5]Minhua Shao, et al. "Boron-doped diamond coated carbon catalyst support." USPatent Application No.2013 / 148,558. Summary of the invention

[0012] In view of the above technical problems, the object of the present invention is to provide a catalyst carrier with high oxygen reduction catalytic activity, comprising a composite catalyst of the catalyst carrier and noble metal particles (e.g., noble metal particles-Fe-NC composite catalyst). The catalyst carrier has a relatively high concentration of transition metal (e.g., Fe) single atoms, a high specific surface area and a high degree of graphitization, and a suitable mesoporous structure, and can uniformly load a high amount of noble metal particles (especially platinum particles) by a simple formic acid reduction method.

[0013] Specifically, the present invention provides the following solutions.

[0014] 1. A catalyst support comprising a mesoporous carbon-containing matrix doped with at least one non-metallic element selected from Groups VA, VIA and VIIA of the Periodic Table of Elements, and further comprising active sites in which at least one transition metal single atom is dispersed.

[0015] Wherein, the non-metallic element is selected from at least one of N, S and P, and / or

[0016] The transition metal is selected from at least one of Fe, Co and Mn.

[0017] Wherein, the specific surface area of ​​the catalyst carrier is 1000-1500m 2 g -1 , and / or

[0018] The pore size of the catalyst carrier is 2-50 nm, preferably 4-7 nm.

[0019] Wherein, relative to the total weight of the catalyst carrier, the content of the transition metal single atom is 1-5% by weight, preferably 2-3% by weight.

[0020] Wherein, relative to the total amount of the catalyst carrier, the doping ratio of the non-metallic element is 5-8 atomic %, and / or the doping ratio of the transition metal is 1-5 atomic %.

[0021] Wherein, the particle size of the catalyst carrier is 50-100nm.

[0022] 2. A composite catalyst comprising

[0023] Any of the above-mentioned catalyst carriers and

[0024] At least one noble metal particle is supported on the catalyst support.

[0025] The noble metal is selected from at least one of Pt, Au, Ir and Ru.

[0026] The loading amount of the noble metal particles is 40-50 wt %, preferably 43-48 wt %, relative to the total weight of the composite catalyst.

[0027] The noble metal particles are uniformly dispersed on the catalyst carrier by formic acid reduction method.

[0028] Preferably, the particle size of the noble metal particles is 2-30 nm, preferably 2-4 nm.

[0029] 3. A method for preparing a composite catalyst, characterized in that it comprises the following steps:

[0030] (1) providing any of the above-mentioned catalyst carriers; and

[0031] (2) The noble metal is uniformly loaded on the catalyst carrier in the form of particles.

[0032] Wherein, the step (1) comprises:

[0033] (i) synthesizing metal-organic framework precursors using metal sources containing metal ions or clusters and organic ligands;

[0034] (ii) sintering the metal-organic framework precursor in an atmosphere containing an inert gas and at least one selected from Groups VA, VIA and VIIA of the periodic table, thereby obtaining the catalyst support.

[0035] Wherein, the metal source comprises transition metal ions, preferably Fe, Zn, Cu or a combination thereof,

[0036] Optionally, the organic ligand is selected from at least one of 2-methylimidazole, imidazole, 2-ethylimidazole and 4-azabenzimidazole.

[0037] Wherein, the step (ii) comprises raising the temperature to 1000-1040°C in an argon environment and maintaining it for 30-60 minutes; after cooling to room temperature, raising the temperature to 900-950°C in an argon environment, switching to an ammonia atmosphere, maintaining it for 10-15 minutes, and then switching to argon to cool to room temperature.

[0038] Wherein, the noble metal is Pt, and the step (2) comprises depositing Pt particles on the catalyst support by a formic acid reduction method.

[0039] The formic acid reduction method comprises reducing platinum particles in an aqueous solution. Preferably, during the reduction of the platinum particles, when formic acid is added dropwise, the solution temperature is maintained at 45-50° C.

[0040] More preferably, during the reduction of the platinum particles, the mixed solution after the formic acid is added dropwise is maintained at 90-98° C. for 60-90 minutes.

[0041] Wherein, the precious metal is Pt, and the step (2) comprises dispersing the catalyst carrier into an aqueous solution, adding a Pt source, heating to 40-50° C. after mixing, then dripping a formic acid solution with a concentration of 30-40 volume %, heating the mixed solution to 90-98° C., and maintaining for 60-90 minutes, thereby uniformly dispersing the Pt particles on the catalyst carrier.

[0042] 4. A fuel cell comprising any of the composite catalysts described above.

[0043] 5. Use of any of the above composite catalysts in fuel cells.

[0044] Beneficial Effects of the Invention

[0045] The present invention uses transition metal atoms-non-metallic elements-mesoporous C containing active sites as a carrier to load precious metal particles for the first time. The present invention also uses a simple formic acid reduction method for the first time to uniformly deposit precious metal particles in the transition metal atom-non-metallic element-mesoporous C carrier. In addition, since the transition metal in the present invention is uniformly dispersed in the non-metallic element-mesoporous C carrier as a single atomic active site, the utilization rate of the active site is improved.

[0046] The present invention also makes the most of the synergistic effect between the carrier and the particles to improve the activity and stability of the catalyst.

[0047] The preparation method of the present invention is simple to operate and eliminates the need for subsequent post-processing of auxiliary agents. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 Shown are (A) the oxygen reduction reaction kinetics and gas and proton mass transfer characteristics of the catalytic layer prepared from nonporous carbon (where the small gray circles represent low-activity platinum particles due to ionomer adsorption); (B) the oxygen reduction reaction kinetics and gas and proton mass transfer characteristics of the catalytic layer prepared from porous carbon (where the small black circles represent platinum particles that cannot participate in the reaction due to excessive material transfer resistance) and (C) the oxygen reduction reaction kinetics and gas and proton mass transfer characteristics of the catalytic layer prepared from reasonable mesoporous carbon (where the small black circles represent platinum particles).

[0049] Figure 2 A high-angle annular dark-field high-resolution scanning transmission electron microscopy image of the catalyst support of Example 1-1 is shown. The white bright spots in the image represent uniformly dispersed Fe single atoms.

[0050] Figure 3 A transmission electron microscopy image of the composite catalyst prepared according to Example 2-1 is shown.

[0051] Figure 4 The current density (mA / cm2) of the catalysts of Example 2-1 and Reference Example is shown. 2 ) versus voltage (volts relative to reversible hydrogen electrode, V vs RHE) polarization curve. Wherein, Pt-Fe-NC represents the composite catalyst prepared in Example 2-1, TKK Pt / C represents the catalyst of the reference example, and Pt-Fe-N-C_10k represents the catalyst of Example 2-1 after 10,000 cycles. TKK Pt / C_10k represents the catalyst of the reference example after 10,000 cycles. The catalyst loading of each catalyst on the test electrode is 51ug / cm 2 .

[0052] Figure 5A transmission electron microscope image of the catalyst particles prepared in Example 3 is shown. DETAILED DESCRIPTION

[0053] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention. If no specific technology or conditions are specified in the embodiments, the technology or conditions described in the literature in this area or the product instructions are used. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0054] Definitions and general terms

[0055] Certain embodiments of the present invention are now described in detail, examples of which are illustrated by the accompanying structural formulas and chemical formulae. The present invention is intended to encompass all substitutions, modifications, and equivalent technical solutions, which are all included within the scope of the present invention as defined in the claims. It should be appreciated by those skilled in the art that many methods and materials similar or equivalent to those described herein can be used to practice the present invention. The present invention is in no way limited to the methods and materials described herein. In the event that one or more of the combined documents, patents, and similar materials differ from or contradict the present application (including but not limited to defined terms, term applications, described technologies, etc.), the present application shall prevail.

[0056] It should be further recognized that certain features of the present invention, which are described in multiple separate embodiments for clarity, may also be provided in combination in a single embodiment. Conversely, various features of the present invention, which are described in a single embodiment for brevity, may also be provided separately or in any suitable sub-combination.

[0057] Unless otherwise specified, all technical terms used in the present invention have the same meaning as commonly understood by those skilled in the art to which the present invention belongs. All patents and publications related to the present invention are incorporated herein by reference in their entirety.

[0058] Unless otherwise specified or there is a clear conflict in context, the articles "a", "an", and "the" as used herein are intended to include "at least one" or "one or more". Therefore, these articles as used herein refer to one or more than one (i.e., at least one) of the objects. For example, "a component" refers to one or more components, i.e., there may be more than one component contemplated for use or use in the implementation of the described embodiment.

[0059] The term "active site" refers to the location on the catalyst or catalyst support that participates in the reaction and is the site where oxygen is adsorbed and a reduction reaction occurs.

[0060] The term "ionomer" refers to ionic polymers used in fuel cell membranes, such as Nafion solutions.

[0061] The term "the catalyst is uniformly dispersed on the catalyst support" means that the catalyst particles are distributed on the catalyst support in a nano state (for example, in the form of individual particles of 2-4 nm).

[0062] The term "single-atom active sites are uniformly dispersed in the catalyst support" means that the transition metal atoms (such as Fe atoms) on the catalyst support are dispersed in the form of single atoms coordinated with the non-metallic elements or C in the catalyst support. This can be demonstrated by the individual white spots in the scanning transmission electron microscope.

[0063] Carbon supports for supporting metal catalysts can include non-porous carbon supports, porous carbon supports and mesoporous carbon supports. Non-porous carbon supports have a high degree of graphitization, a medium specific surface area, and good material transfer efficiency and resistance to substrate oxidation. However, the metal catalyst particles supported by this non-porous carbon support are generally distributed on the carbon surface and are easily poisoned by ionomers (such as Nafion solution). Figure 1 (A)). For porous carbon, if the pore size is too small, the ionomer can be prevented from entering the pores and deactivating the metal catalyst particles, but at the same time, the transport resistance of the oxidizing substances is increased, making the catalyst particles unable to participate in the reaction ( Figure 1 (B)). Carbon supports with suitable mesoporous structures can prevent the ionomer from directly contacting the metal catalyst particles while not hindering the transmission of oxygen ( Figure 1 (C)). The carbon support also affects the stability of the fuel cell catalyst. For precious metal (such as Au, Pt, etc.) based catalysts, the poor stability is mainly due to the attenuation of the electrochemical active area caused by the dissolution and agglomeration of the precious metal particles. Generally speaking, in addition to the instability of the catalyst itself, such as too small particle size, carbon oxidation is the direct cause of the dissolution of precious metal particles. Because agglomeration involves the migration of particles on the surface of the carbon support, a higher carbon porosity can reasonably reduce the occurrence of agglomeration.

[0064] Based on the above, the present invention provides a catalyst support, which comprises a mesoporous carbon-containing matrix doped with at least one non-metallic element selected from Groups VA, VIA and VIIA of the periodic table, and further comprises active sites dispersed with at least one transition metal single atom.

[0065] Preferably, the non-metal element is selected from at least one of N, S and P. The transition metal may be selected from at least one of Fe, Co and Mn.

[0066] Preferably, the catalyst carrier of the present invention is a carrier having a high concentration of transition metal single atoms, a high specific surface area and a graphitization degree and a suitable mesoporous structure. The catalyst carrier is uniformly loaded with high-loaded noble metal (such as Au, Pt) particles by a simple formic acid reduction method.

[0067] For example, the specific surface area of ​​the catalyst support may be 1000-1500m 2 g -1 The pore size of the catalyst support may be 2-50 nm, preferably 4-7 nm.

[0068] In one example, the content of transition metal atoms is 1-5% by weight, preferably 2-3% by weight, relative to the total weight of the catalyst carrier. The doping ratio of the non-metallic element is 5-8 atomic % relative to the total amount of the catalyst carrier. The doping ratio of the transition metal can be 1-5 atomic %.

[0069] After drying, the catalyst support may be in the form of a fine powder. The particle size of the catalyst support may be 50-100 nm.

[0070] The catalyst support may have uniformly distributed active sites, and preferably, the transition metal atoms (such as Fe atoms) on the catalyst support are coordinated and dispersed with the non-metallic elements or C in the catalyst support in the form of single atoms. This can be demonstrated by individual white spots in a scanning transmission electron microscope.

[0071] In a preferred embodiment, the catalyst support of the present invention is a Fe-NC support having a relatively high concentration of Fe single atoms, a high specific surface area and a degree of graphitization and a suitable mesoporous structure.

[0072] The Fe-NC carrier of the present invention exhibits superior oxygen reduction activity and stability compared to existing non-precious metal catalysts, and thus can be used as a suitable active carrier in a composite catalyst.

[0073] Therefore, in another aspect, the present invention provides a composite catalyst, which comprises any of the above-mentioned catalyst carriers and at least one noble metal particle supported on the catalyst carrier.

[0074] The noble metal may be at least one selected from the group consisting of Pt, Au, Ir, and Ru.

[0075] The loading amount of the noble metal particles may be 40-50 wt %, preferably 43-48 wt %, relative to the total weight of the composite catalyst.

[0076] Preferably, the noble metal particles are uniformly dispersed on the catalyst carrier by formic acid reduction, thereby enabling uniform deposition of the noble metal particles, thereby synthesizing a composite catalyst having abundant active sites, balanced pores, uniform dispersion of the noble metal particles, and excellent activity and stability.

[0077] Preferably, the particle size of the precious metal particles supported on the catalyst carrier is 2-30 nm, preferably 2-4 nm.

[0078] Preferably, the Fe-NC carrier in the composite catalyst has a single Fe atom concentration of 2-3 wt%. Furthermore, the Pt particles in the composite catalyst are loaded on the Fe-NC by a simple formic acid reduction method in an aqueous solution, and the Pt loading is as high as 45%.

[0079] In another aspect, the present invention also provides a method for preparing a composite catalyst, comprising the following steps: (1) providing any of the above-mentioned catalyst carriers; and (2) uniformly loading the noble metal on the catalyst carrier in the form of particles.

[0080] Preferably, the step (1) comprises:

[0081] (i) synthesizing a metal-organic framework precursor using a metal source containing metal ions or clusters and an organic ligand; and

[0082] (ii) sintering the metal-organic framework precursor in an atmosphere containing an inert gas and at least one selected from Groups VA, VIA and VIIA of the periodic table, thereby obtaining the catalyst support.

[0083] Wherein, the metal source may contain transition metal ions, preferably Fe, Zn, Cu or a combination thereof,

[0084] Optionally, the organic ligand is selected from at least one of 2-methylimidazole, imidazole, 2-ethylimidazole and 4-azabenzimidazole.

[0085] Wherein, step (ii) may include raising the temperature to 1000-1040°C in an argon environment and maintaining it for 30-60 minutes; after cooling to room temperature, raising the temperature to 900-950°C in an argon environment, switching to an ammonia atmosphere, maintaining it for 10-15 minutes, and then switching to argon to cool to room temperature.

[0086] In a specific embodiment, 200-300 mg of Fe-doped ZIF-8 precursor is subjected to high temperature pyrolysis, first raised to 1000°C in an argon environment and maintained for 30-60 minutes. After cooling to room temperature, the temperature is raised to 900°C in an argon environment, switched to an ammonia atmosphere, maintained for 10-15 minutes, and then cooled to room temperature with argon. Thus, a black powdery Fe-NC carrier is obtained with a yield of 30-50%.

[0087] Wherein, the noble metal is Pt, and the step (2) comprises depositing Pt particles on the catalyst support by a formic acid reduction method.

[0088] The formic acid reduction method comprises reducing platinum particles in an aqueous solution. Preferably, during the reduction of the platinum particles, when formic acid is added dropwise, the solution temperature is maintained at 45-50° C.

[0089] More preferably, during the reduction of the platinum particles, the mixed solution after the formic acid is added dropwise is maintained at 90-98° C. for 60-90 minutes.

[0090] When the precious metal is Pt, the step (2) comprises dispersing the catalyst carrier into an aqueous solution, adding a Pt source, heating to 40-50° C. after mixing, then dripping a formic acid solution having a concentration of 30-40% by volume, heating the mixed solution to 90-98° C., and maintaining the temperature for 60-90 minutes, thereby uniformly dispersing the Pt particles on the catalyst carrier.

[0091] In a specific embodiment, the present invention provides a method for preparing a Fe-NC supported platinum composite catalyst having high oxygen reduction catalytic activity and stability, comprising the following steps:

[0092] Zinc nitrate and ferrous sulfate as metal sources and 2-methylimidazole as ligand were dissolved in a certain amount of methanol solution, and after removing oxygen from the solution in an argon environment, the two were mixed and stirred at 40-45°C to form a Fe-doped ZIF-8 precursor. The excess unreacted metal source and ligand were removed by centrifugation and placed in a vacuum oven for drying. The precursor was directly subjected to high-temperature argon and ammonia heat treatment to obtain a Fe-NC carrier.

[0093] The heat-treated Fe-NC is uniformly dispersed in an aqueous solution, and the diluted chloroplatinic acid solution is added dropwise to the carrier solution and mixed evenly. After the solution is heated to a certain temperature, a certain amount of formic acid is slowly added dropwise, and then the mixed solution is heated to a higher temperature and maintained for a certain period of time to completely reduce the platinum source. The excess unreacted platinum source is collected by centrifugation and removed with water, and then placed in a vacuum oven for drying.

[0094] This method uses Fe-NC as a carrier to load platinum particles, which can not only improve the activity density of the catalyst, but also solve the shortcomings of the existing methods for preparing precious metal catalysts, which have low treatment efficiency and require complex post-treatment processes. In addition, the method of the present invention uses water as a solvent, and the synthesis method is simple, which is conducive to industrial promotion.

[0095] Furthermore, the Fe-NC support is prepared by high-temperature sintering of a Fe-doped ZIF-8 precursor using zinc nitrate and ferrous sulfate as metal sources and 2-methylimidazole as a ligand chelate in an argon and ammonia atmosphere.

[0096] Furthermore, the Fe-NC carrier has a high specific surface area and a suitable mesoporous structure. For example, the specific surface area of ​​the Fe-NC carrier can be 1000-1500m 2 g -1 The pore size of the mesoporous structure may be 2-50 nm, preferably 4-7 nm.

[0097] Further, the high temperature argon heat treatment of the Fe-NC support comprises the following steps: maintaining the temperature at 1000-1040°C for 30-60 minutes in an Ar atmosphere.

[0098] Furthermore, the high temperature ammonia heat treatment of the Fe-NC carrier comprises the following steps: heating to 900-950° C. in an Ar atmosphere, switching to ammonia and maintaining for 10-15 minutes, and cooling to room temperature in an Ar atmosphere.

[0099] Furthermore, the reduction of the platinum particles is carried out in an aqueous solution.

[0100] Furthermore, during the reduction of the platinum particles, the solution temperature was maintained at 45-50°C when formic acid was added dropwise.

[0101] Furthermore, during the reduction of the platinum particles, the mixed solution after the formic acid is added is maintained at 90-98° C. for 60-90 minutes.

[0102] In another aspect, the present invention also provides a fuel cell. The fuel cell may include a cathode, an anode, a proton membrane, a gas diffusion layer, and a bipolar plate. When the fuel cell is working, the composite catalyst of the present invention can be used as a catalyst for the cathode and catalyze the reduction of oxygen into water.

[0103] The present invention also provides the use of any of the above-mentioned composite catalysts in a fuel cell.

[0104] In summary, the present invention is the first to use a catalyst carrier containing active sites to load platinum and other precious metal particles, and the first to use a simple formic acid reduction method to uniformly deposit platinum and other precious metal particles in the catalyst carrier. In addition, since the single-atom active sites in the present invention are uniformly dispersed in the catalyst carrier, the utilization rate of the active sites is improved. The synergistic effect between the carrier and the particles is maximized to improve the activity and stability of the catalyst. The preparation method of the present invention is simple to operate and eliminates the subsequent post-treatment process of the auxiliary agent.

[0105] The present invention is further explained or illustrated by way of examples below, but these examples should not be construed as limiting the scope of protection of the present invention.

[0106] example

[0107] Example 1-1

[0108] First, prepare the Fe-doped ZIF-8 carrier. 8g of zinc nitrate mixed with 10mg of ferrous sulfate as a metal source and 20g of 2-methylimidazole as a ligand were dissolved in 50ml and 100mL of methanol solution respectively, and the oxygen in the solution was removed by bubbling in an Ar atmosphere for 0.5-1h. The two were mixed and stirred at 40°C for 8-10 hours to chelate into a light gray Fe-doped ZIF-8 precursor. The excess unreacted metal source and ligand were removed by centrifugation and washed three times with anhydrous alcohol, and then placed in a vacuum oven at 60-70°C for 10-12 hours for drying.

[0109] After that, 200 mg of Fe-doped ZIF-8 precursor was pyrolyzed at high temperature, firstly raised to 1000°C in an argon environment and maintained for 30 minutes. After cooling to room temperature, it was heated to 900°C in an argon environment, switched to an ammonia atmosphere, maintained for 10 minutes, and then cooled to room temperature by switching to argon. Thus, a black powdery Fe-NC carrier was obtained with a yield of 30%.

[0110] Figure 2 A high-angle annular dark-field high-resolution scanning transmission electron micrograph of the Fe-NC carbon support of Example 1-1 is shown. The white bright spots in the figure represent uniformly dispersed Fe single atoms. Test method: The catalyst support powder is dispersed in an ethanol solution and then dripped onto a copper grid, and characterized in a scanning transmission electron microscope of model "FEI Themis G2".

[0111] The above indicates that the catalyst carrier has transition metal active sites uniformly dispersed in the form of single molecules.

[0112] Example 1-2 - Example 1-5

[0113] The catalyst carrier of Example 1-1-1-5 was prepared in the same manner as in Example 1, except that the preparation conditions were changed according to the parameters shown in the attached Table 1. The yield and form of the obtained catalyst carrier are shown in Table 1.

[0114] Example 2-1

[0115] 20 mg of the Fe-NC carrier in Example 1-1 was dispersed in 20 ml of aqueous solution. 70 mg of chloroplatinic acid hexahydrate was first diluted with 30 mL of aqueous solution, and then slowly added dropwise to the stirred solution of the Fe-NC carrier (30 minutes). The mixed solution was heated to 40 ° C, and 10 mL of a 30-40% formic acid solution was slowly added dropwise (30 minutes), and the mixed solution was further heated to 90-98 ° C and maintained for 60-90 minutes. Thus, 30 mg of Fe-NC platinum-supported composite catalyst was obtained. The Pt loading of the catalyst of this embodiment was 46% by weight as determined by inductively coupled plasma (ICP) method.

[0116] Figure 3 The transmission electron micrograph of the composite catalyst of Example 2-1 shows that platinum particles are uniformly dispersed on a carbon substrate by formic acid reduction. Test method: The catalyst powder is dispersed in an ethanol solution and then dripped onto a copper grid, and characterized using a transmission electron microscope of model "JEOL2010F".

[0117] The results showed that the platinum particles were uniformly dispersed onto the catalyst support in the form of monodisperse nanoparticles of 2-4 nm without agglomerating into large particles.

[0118] Example 2-2-Example 2-5

[0119] The composite catalyst supports of Examples 2-2 to 2-5 were prepared in the same manner as in Example 2-1, except that the preparation conditions were changed according to the parameters shown in the attached Table 2. As a result, the obtained composite catalysts were in the form of black powders, and the yield was 30% to 50%.

[0120] Observation by a "JEOL 2010F" transmission electron microscope indicated that the composite catalysts obtained in these examples were obtained in which platinum particles were uniformly dispersed on the catalyst carrier in the form of monodispersed nanoparticles of 2-4 nm.

[0121] Example 3

[0122] Using the Fe-NC of Example 1-1 as a carbon substrate, platinum particles were reduced by an organic solution of oleylamine and oleic acid at 190° C. to obtain catalyst powder. Figure 5 The transmission electron microscope image of the composite catalyst prepared in this embodiment is shown. Figure 5As shown in the figure, the Pt particles cannot be evenly dispersed on the carbon substrate. This indicates that the formic acid reduction method in aqueous solution can more effectively deposit small-sized Pt particles evenly on the Fe-NC substrate.

[0123] Embodiment 2-6

[0124] The composite catalyst support of Example 2-6 was prepared in the same manner as Example 2-1, except that the Fe-NC support was replaced with the Co-NC support of Example 1-4 as shown in Table 3. As a result, the obtained composite catalyst was in the form of black powder, and the yield was 40%.

[0125] Through observation by a transmission electron microscope of model "JEOL 2010F", the composite catalyst obtained in this embodiment is a composite catalyst in which platinum particles are uniformly dispersed on the catalyst carrier in the form of monodispersed nanoparticles of 2-4 nm.

[0126] Reference example

[0127] The reference example is a commercial Pt / C catalyst purchased from Tanaka Kikinzoku International (TKK) Co., Ltd.

[0128] Comparative Example 1

[0129] Commercial porous Ketjen carbon was used as the substrate to reduce the platinum particles by the same formic acid reduction method. The transmission electron microscope (TEM) of model "JEOL 2010F" showed that the platinum particles agglomerated to a certain extent at a platinum loading of 40-50%.

[0130] Test Example 1

[0131] The Fe-NC platinum-supported catalysts prepared in Example 2-1 and Example 2-6 were subjected to electrochemical testing in 0.1M HClO4 solution. The test method is to first disperse 5 mg of catalyst powder in 4 mL of isopropanol and 1 ml of ultrapure water solution, and then add 20 μL of a 5 wt% ionomer solution and mix them evenly by ultrasonic mixing. A 5 mm diameter platinum carbon electrode was used as the working electrode, 10 μL of the mixed slurry was added dropwise and then dried naturally. The carbon rod and Ag / AgCl were used as the counter electrode and reference electrode, respectively. In an oxygen-saturated solution, the working electrode was rotated at 1600 rpm, and linear sweep voltammetry was used to scan from 0.125 V to 1.0 V at a scan rate of 10 mV / s to obtain the polarization curve of the catalyst. The platinum mass activity of the catalyst at a potential of 0.9 V was calculated by the Koutecky-Levich formula:

[0132] 1 / j=1 / j_k+1 / j_l

[0133] Where j is the current density obtained by the test, j_l is the limiting current density corresponding to Figure 4 The current density when the polarization curve reaches the platform. j_k is the kinetic current density to be calculated. The value obtained by j_k relative to the platinum loading on the electrode is the mass activity of platinum. The mass activity of platinum in Example 2-1 is calculated to be 0.28A mg -1 , the mass activity of Example 2-6 is 0.23A mg -1 , which is much larger than the 0.18A mg of commercial platinum carbon (reference example) -1 .

[0134] In addition, the platinum mass activity of the platinum catalyst of Comparative Example 1 is 0.16-0.18 A mg -1 , not better than the commercial Pt / C catalyst (reference example).

[0135] The above results show that the active support plays a vital role in improving the activity of the composite catalyst.

[0136] The catalyst of Example 2-1 and the catalyst of Reference Example were tested for stability in an oxygen-saturated 0.1M HClO4 solution. The working electrode was tested for 10,000 cycles (10k) at a potential range of 0.6-1.0V and a scan rate of 50mV / s. The changes in the polarization curves of the catalysts at the beginning and after the cycles were compared and analyzed. The results are shown in FIG. Figure 4 As shown, the Pt-Fe-NC of Example 2-1 exhibits good stability, and the initial and cycled polarization curves are basically consistent; while the polarization curve of the reference example after cycle shifted negatively by 7-10 mV.

[0137] Test Example 2

[0138] The electrochemical test method of Test Example 1 was also used to obtain the polarization curves of Example 2-1, Example 1-1 and pure Pt particles under the same conditions, and their corresponding half-wave potentials (V), that is, the voltage corresponding to half of the limiting current, were calculated respectively. The results are shown in Table 1 below:

[0139] Table 1

[0140] Catalyst type Half-wave potential (V) Example 2-1 (Pt loading 46%) 0.89-0.90 Example 1-1 (Catalyst carrier) 0.80 Pt particles 0.86

[0141] The half-wave potential is an important parameter reflecting the catalytic activity. The above results show that the catalyst activity of Example 2-1 is greater than the sum of the expected catalyst activities of the catalyst carrier + Pt particles, thus proving that a synergistic effect occurs between the catalyst carrier and the Pt particles.

[0142] in conclusion

[0143] As shown in the above embodiments and comparative examples, the present invention uses a catalyst carrier containing active sites to load platinum and other precious metal particles, and can uniformly deposit platinum and other precious metal particles in the catalyst carrier. In addition, the single-atom active sites are uniformly dispersed in the catalyst carrier, thereby improving the utilization rate of the active sites. Moreover, a synergistic effect is achieved between the catalyst carrier and the precious metal particles to improve the activity and stability of the catalyst.

[0144]

[0145]

[0146]

Claims

1. A composite catalyst having oxygen reduction catalytic activity, characterized in that Include: A catalyst support, comprising a mesoporous carbon-containing matrix doped with a non-metallic element and further comprising active sites dispersed with transition metal single atoms, wherein the content of the transition metal single atoms is 1-5 wt % relative to the total weight of the catalyst support; and At least one noble metal particle loaded on the catalyst carrier, wherein the loading amount of the noble metal particle is 40-50% by weight relative to the total weight of the composite catalyst, wherein the noble metal particle is a Pt particle, wherein the Pt particle is uniformly dispersed on the catalyst carrier by a formic acid reduction method, the reduction is complete reduction, and the particle size of the Pt particle is 2-4 nm; The non-metallic element is selected from N, the transition metal is selected from at least one of Fe and Co, the doping ratio of the non-metallic element is 5-8 atomic %, and the doping ratio of the transition metal is 1-5 atomic % relative to the total amount of the catalyst carrier, and the pore size of the catalyst carrier is 4-50 nm and the specific surface area is 1000-1500 m 2 g -1 .

2. The composite catalyst according to claim 1, characterized in that The loading amount of the noble metal particles is 43-48 wt % relative to the total weight of the composite catalyst.

3. The composite catalyst according to claim 1, characterized in that The pore size of the catalyst carrier is 4-7 nm.

4. The composite catalyst according to any one of claims 1 to 2, characterized in that The content of the transition metal single atom is 2-3 wt % relative to the total weight of the catalyst carrier.

5. The composite catalyst according to any one of claims 1 to 2, characterized in that The particle size of the catalyst carrier is 50-100 nm.

6. A method for preparing a composite catalyst, characterized in that The following steps are involved: (1) providing a catalyst support, the catalyst support comprising a mesoporous carbon-containing matrix doped with a non-metallic element and further comprising active sites dispersed with transition metal single atoms, wherein the content of the transition metal single atoms is 1-5 wt % relative to the total weight of the catalyst support; and (2) uniformly loading the noble metal on the catalyst carrier in the form of particles, wherein the loading amount of the noble metal particles is 40-50% by weight relative to the total weight of the composite catalyst, wherein the noble metal particles are Pt particles, wherein the step (2) comprises depositing the Pt particles on the catalyst carrier by a formic acid reduction method, wherein the reduction is complete reduction, and the particle size of the Pt particles is 2-4 nm; The non-metallic element is selected from N, the transition metal is selected from at least one of Fe and Co, the doping ratio of the non-metallic element is 5-8 atomic %, and the doping ratio of the transition metal is 1-5 atomic % relative to the total amount of the catalyst carrier, and the pore size of the catalyst carrier is 4-50 nm and the specific surface area is 1000-1500 m 2 g -1 .

7. The method for preparing a composite catalyst according to claim 6, characterized in that The step (1) comprises: (i) synthesizing metal-organic framework precursors using metal sources containing metal ions or clusters and organic ligands; (ii) sintering the metal-organic framework precursor in an atmosphere containing an inert gas and ammonia, thereby obtaining the catalyst support.

8. The method for preparing a composite catalyst according to claim 7, characterized in that The metal source comprises a transition metal ion, Optionally, the organic ligand is selected from at least one of 2-methylimidazole, imidazole, 2-ethylimidazole and 4-azabenzimidazole.

9. The method for preparing a composite catalyst according to claim 7, characterized in that The step (ii) comprises raising the temperature to 1000-1040° C. in an argon environment and maintaining it for 30-60 minutes; after cooling to room temperature, raising the temperature to 900-950° C. in an argon environment, switching to an ammonia atmosphere, maintaining it for 10-15 minutes, and then switching to argon to cool to room temperature.

10. The method for preparing a composite catalyst according to claim 6, characterized in that The formic acid reduction method includes reducing platinum particles in an aqueous solution.

11. The method for preparing a composite catalyst according to claim 6, characterized in that The step (2) comprises dispersing the catalyst carrier into an aqueous solution, adding a Pt source, heating to 40-50° C. after mixing, then dripping a formic acid solution having a concentration of 30-40% by volume, heating the mixed solution to 90-98° C., and maintaining the temperature for 60-90 minutes, thereby uniformly dispersing the Pt particles on the catalyst carrier.

12. The method for preparing a composite catalyst according to claim 7, characterized in that The metal source comprises a transition metal ion selected from Fe, Zn, Cu or a combination thereof.

13. The method for preparing a composite catalyst according to claim 10, characterized in that During the reduction of the platinum particles, the solution temperature was maintained at 45-50°C when formic acid was added dropwise.

14. The method for preparing a composite catalyst according to claim 10, characterized in that During the reduction process of the platinum particles, the mixed solution after the formic acid is added is maintained at 90-98° C. for 60-90 minutes.

15. A fuel cell comprising the composite catalyst according to any one of claims 1 to 5.

16. Use of the composite catalyst according to any one of claims 1 to 5 in a fuel cell.

Citation Information

Patent Citations

  • Low power node dormant state

    US20130148558A1

  • Fuel cell electrode comprising conductive zeolite support material

    US6117581A

  • Preparation method for metal-organic-framework-loaded platinum-based catalyst

    CN105958085A

  • P / metal-n-c hybrid catalyst

    CN108352533A

  • Iron and nitrogen co-doped carbon-oxygen reduction catalyst, and preparation method and application thereof

    CN109103468A